2019
DOI: 10.1038/s41579-018-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus: an overview of basic and clinical research

Abstract: First identified in purulent fluid from a leg abscess by Ogston in the 1880s and formally isolated by Rosenbach not long after, Staphylococcus aureus is well adapted to its human host and the health-care environment 1. S. aureus is both a frequent commensal and a leading cause of endocarditis, bacteraemia, osteomyelitis and skin and soft tissue infections. With the rise of hospital-based medicine, S. aureus quickly became a leading cause of healthcare-associated infections as well. Penicillin offered short-liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
1,041
2
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,363 publications
(1,081 citation statements)
references
References 204 publications
(139 reference statements)
10
1,041
2
28
Order By: Relevance
“…Methicillin‐resistant Staphylococcus aureus causes various diseases such as skin and soft tissue infections, endocarditis, and bone and joint infections . Among these infections, MRSA bacteremia (MRSAB) is one of the most common problems because of the associated high mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin‐resistant Staphylococcus aureus causes various diseases such as skin and soft tissue infections, endocarditis, and bone and joint infections . Among these infections, MRSA bacteremia (MRSAB) is one of the most common problems because of the associated high mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is a bacterial pathogen of humans and livestock. It is encountered as a β‐lactam‐susceptible strain (referred to customarily as methicillin‐susceptible S. aureus , MSSA) and as β‐lactam‐resistant strains (MRSA, encountered as a variety of strains) . Here, methicillin refers to a specific second‐generation penicillin that was developed decades ago as especially active against MSSA, as a result of its stability to the hydrolytic deactivation of its β‐lactam substructure (in contrast to first‐generation penicillins) as catalyzed by a plasmid‐encoded β‐lactamase (BlaZ).…”
Section: Sensing and Evading The β‐Lactam Antibiotics By A Gram‐positmentioning
confidence: 99%
“…MRSA are resistant to all but the most recent β‐lactams. Accordingly, their problematic chemotherapy requires an oxazolidinone (linezolid), one of the newest β‐lactams, or older drugs (such as daptomycin or vancomycin) whose clinical development was renewed in response to the need for anti‐MRSA agents . Resistance to each of these clinically‐used antibiotics is encountered.…”
Section: Sensing and Evading The β‐Lactam Antibiotics By A Gram‐positmentioning
confidence: 99%
“…Mortality rates for patients with Staphylococcus aureus bacteraemia (SAB) largely remain unchanged despite significant advances in clinical management, with new antibiotic therapies and rapid diagnostics available in recent decades. Significant heterogeneity in the clinical course of patients with SAB despite appropriate antibiotic therapy suggests that differential host immune response may contribute to adverse patient outcomes . However, critical determinants of immune evasion in patients with SAB remain poorly understood and connections between the immune response and microbiological failure are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Significant heterogeneity in the clinical course of patients with SAB despite appropriate antibiotic therapy suggests that differential host immune response may contribute to adverse patient outcomes. [1][2][3] However, critical determinants of immune evasion in patients with SAB remain poorly understood and connections between the immune response and microbiological failure are lacking. Previous studies identified several candidate innate immunity biomarkers that were independently associated with mortality and prolonged SAB, supporting the utility of biomarkers to distinguish patients prone to developing severe disease.…”
Section: Introductionmentioning
confidence: 99%